El yacimiento de Las Camas, Villaverde, Madrid Longhouses y elementos orientalizantes al inicio de la Edad del Hierro, en el valle medio del Tajo - Urbina, Dionisio; Morín, Jorge; Ruiz, Luis A.; Agustí, Ernesto; Montero, Ignacio (Gerión. Revista de Historia Antigua, 2008)
An archaeological work that implied the clear of a great extension of land, permitted to document in Villaverde Madrid, for the first time in the Iberian Peninsula the existence of a habitat formed for two large hut or long houses similar to the longhouses of Central Europe. This fact opens new perspectives for the study of the settlement at the start of the Iron Age in the Middle Tajo Valley, moment that the analyses of C14 permit us to carry to the full century IX b.C. Among the materials found emphasizes a graphite that could be interpreted as copy of a Phoenician letter, which, next to other elements of oriental inspiration, seem to indicate us the existence of a commercial traffic already very flowed, in whose circuits begins to verify in some way, the Phoenician presence in the peninsular south.